KAJIAN PENELITIAN ANALISIS BEBAN KERJA DAN KEBUTUHAN PEGAWAI PERUSAHAAN DAERAH PADA PERUSAHAAN DAERAH BANK PERKREDITAN RAKYAT KOTAMADYA UJUNG PANDANG (PD. BPR KMUP) KOTA MAKASSAR - M. Rustan DM; Abdullah Abdullah (AkMen JURNAL ILMIAH, 2017)
The results of this study indicate that PD. BPR-KMUP Makassar City in the year 2016 has a total workload (BK) of 30,977 People Hours (OJ) with the time of completion of work (WP) of 20,357 People Hour (OJ) with the number of employee needs as many as 24 people, while there are 17 employees So that PD BPR-KMUP Makassar City lacks 7 (seven) employees with the following details: (1). The finance department has no vacancy; (2). General Section lacks 2 (two) employees; (3). Credit Section lacks 3 (three) employees; (4). The Supervisory Section does not have a Vocation of Position; (5). The cash office lacks 2 (two) employees. The shortage of the staff consists of the General Section of the shortage of two employees, namely Driver and Security, Credit Section Lack of 3 (three) people of Funding / Landing, while in Cash Office lack of 2 (two) officers / officers Namely Head of Cash Office and Customer Service (CS). Employee deficiency in the general part of the driver due to PD. BPR KMUP Kota Makassar does not have a Driver while the driver has a workload of 1,280 People Hours (OJ), while Security shortage is charged because Security has a 24 hour workload per day or 3,074 Hours (OJ) per year while The current security is only 1 (one) person. Employee losses on the credit section are due to vacancy in the Funding / Lending staff, while the funding / lending staff has 2,760 Hours (OJ) per year. With the shortage of employees this causes the effectiveness and efficiency of Unit (EU) to be disrupted in the end affect the Work Performance Unit (PU), this can be seen from the Performance Funding and Landing on PD. BPR KMUP Kota Makassar which only realized 17% for Funding and 52% for Landing respectively from the initial target stated in PDK PD. BPR KMUP Kota Makassar Year 2016. Employee / Cash Officials' lack of office is caused by vacant position of Head of Cash Office and Customer Service (CS), while each Head of Cash Office has workload of 1,340 Hours (OJ) And Customer service has 1,140 People Hours (OJ). In the absence of the head of the Office of Cash and Customer Service (CS) makes the Effectiveness and Efficiency Unit (EU) and performance at the cash office to be disrupted which ultimately adds to the workload for existing employees. In addition to referring to Workload Analysis (ABK), the fulfillment of employee needs on PD. BPR-KMUP Makassar City also needs to consider and anticipate the existence of organizational structure changes in PD. BPR-KMUP Kota Makassar includes the plan of opening of Branch Offices and Cash Offices in every Sub-District in Makassar City, and the presence of employees who have entered retirement and optimizing the execution of duties in each section and cash office.